Paradigm Shift of Statistical Big Data in Healthcare: Management, Analysis and Future Prospects - Dila Ram Bhandari,; Ron Kenett, (Pravaha, 2022)
‘Big data’ is vast describing volumes of information that can work miracles. Multiple attempts designed at highlighting the relationship between big data analytics and benefits for healthcare organizations have been raised. The big data influence on health organization management is still not clear due to the relationship’s multi-disciplinary nature. It has become a topic of special interest for the past two decades because of a great potential that is hidden in it. Numerous public and private sector industries generate, store, and analyze big data with an aim to improve the services they provide. In the healthcare industry, various sources for big data include hospital records, medical records of patients, results of medical checkups, and devices that are a part of internet of things. Biomedical research also produces a significant share of big data pertinent to public healthcare. Big Data and healthcare are precarious to discourse the risk of hospitalization. This data requires proper management and analysis in order to derive expressive communication. There are various encounters associated with each step of handling big data which can only be surpassed by using high-end computing solutions for big data analysis. Providing relevant results for improving public health, healthcare providers are required to be fully equipped with appropriate infrastructure to systematically generate and analyze big data. A well-organized management, analysis, and interpretation of big data can transformation the game by opening new avenues for contemporary healthcare. With a strong integration of biomedical and healthcare data, modern healthcare institutes can probably revolutionize the medical therapies and personalized medicine.